Historical Spatial Distribution of Zoonotic Diseases in Domestic, Synanthropic, and Wild Animals in the Mexican Territory of the Yucatan Peninsula - Paulina Haro; Enrique Trasviña-Muñoz; Irving May-Concha; Gilberto López-Valencia; Francisco Monge-Navarro; Carloman Herrera-Ramírez; Julio A. Mercado-Rodríguez; Hernán Villanueva-Alonzo; Etienne Waleckx (Journal of Tropical Medicine)
The Mexican territory of the Yucatan Peninsula has a tropical climate and harbors a wide variety of domestic, synanthropic, and wild animals, as well as disease vectors. To determine the distribution of recorded zoonotic diseases in the Yucatan Peninsula, scientific publications referring to these diseases in animals and containing geographic coordinates of disease occurrence, were studied. The epidemiological bulletins of the national government were also consulted to obtain information on zoonotic diseases reported in humans in the territory. The territory harbors a wide variety of tropical zoonotic pathogens, including Trypanosoma cruzi, Leptospira interrogans, Toxoplasma gondii, Leishmania mexicana, Dirofilaria immitis, and Rickettsia felis. A variety of domestic, synanthropic, and wild animals act as hosts or reservoirs in the transmission cycle of the zoonotic diseases in the Yucatan Peninsula, and some spillover into human populations has also been recorded. There are still zoonotic diseases that have rarely or never been reported in humans, but it is not clear whether this is because these diseases in humans are not common, there is a lack of viable transmission cycle or there is a lack of appropriate diagnosis. It is necessary to continue monitoring vectors, animal hosts, and humans to identify risk factors for zoonotic diseases in the Yucatan Peninsula.